FRI0267 A Prediction Model That Identifies Patients Most Likely to Benefit from First-Line Therapy with Adalimumab plus Methotrexate in Early Rheumatoid Arthritis. (10th June 2014) - van Vollenhoven, R.F.; Betts, K.; Signorovitch, J.; Bao, C.; Shaw, J.W.; Ganguli, A.
Abstract : Background: In early rheumatoid arthritis (RA), adalimumab (ADA) + methotrexate (MTX) as first-line treatment yields superior clinical and radiological outcomes versus MTX monotherapy but entails risk for overtreatment and high costs. Therefore, current treatment guidelines limit such use to patients with a poor prognosis. The objective of this study was to develop a scoring algorithm to identify patients at high risk of radiographic progression with MTX monotherapy and assess the benefit of first-line ADA+MTX treatment in this subset. Methods: The Optimal Protocol for Treatment Initiation with MTX and ADA (OPTIMA) trial was used. In order to predict the probability of radiographic progression (increase in total sharp score >0.5 at week 26) as a function of patient baseline clinical characteristics, a scoring algorithm was developed in 246 patients randomly selected out of a total of 498 MTX-treated patients, using the least absolute shrinkage and selection operator (LASSO) method. The remaining 252 MTX-treated patients and all 493 ADA+MTX treated patients, a total of 745 (i.e. the evaluation sample), were then used to identify patients at high risk for radiographic progression by ranking the predicted probability of progression based on the scoring algorithm. The top 50% of the evaluation sample in terms of probability of progression were considered the high risk group and were compared to the entire OPTIMA trial population with respect to radiographic progression, American College of Rheumatology (ACR) response rates, and the cost per progression avoided (CPPA) was estimated from a societal perspective. Results: Seven baseline characteristics were found to be significant predictors for radiographic progression and were used to form the scoring algorithm: body mass index, RA duration, tender joint count based on 28 joints, patient rating of pain, C-reactive protein, and joint space narrowing and erosion scores. In the group of patients at high risk for radiographic progression ADA+MTX had 23.2% lower observed radiographic progression compared with MTX, a significantly greater difference relative to the 14.9% difference observed in the full OPTIMA patient sample (P=0.01). Similarly, the difference in ACR20 was 15.4% versus 10.5%, and the CPPA was £16, 357 versus £26, 356, both in favor of ADA+MTX. Conclusions: A scoring algorithm was developed, based on seven simple clinical parameters that predicted radiographic progression with first-line MTX. Patients at high risk for radiographic progression according to this algorithm had greater treatment benefits with first line ADA+MTX versus MTX alone compared to the overall population of MTX naïve early RA patients. These results support the principle that individualized treatment can be both more effective and more cost-effective. Acknowledgements: The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: R. van Vollenhoven Grant/research support: AbbVie, BMS, GSK, Pfizer, Roche, UCB, Consultant for: AbbVie, Biotest, BMS, GSK, Lilly, Merck, Pfizer, Roche, UCB, Vertex, K. Betts Employee of: Analysis Group, which has received consulting fee from AbbVie to partner on this research, J. Signorovitch Employee of: Analysis Group, which has received consulting fee from AbbVie to partner on this research, C. Bao Shareholder of: AbbVie, Employee of: AbbVie, J. Shaw Shareholder of: AbbVie, Employee of: BMS, former employee of AbbVie, A. Ganguli Shareholder of: AbbVie, Employee of: AbbVie DOI: 10.1136/annrheumdis-2014-eular.1462